Why some firms succeed in exporting while others do not? The impact of resources and capabilities on firms' export performance - Simões, Luís Carlos Ganhão (2012)
Why do some firms succeed in exporting while others do not? Export activities are a crucial area of international business but the drivers of superior export performance are not yet well understood. In this study, employing a sample of 52 Portuguese firms, we examine what are the distinctive resources and capabilities associated to superior export performance through the establishment of sustainable competitive advantages. Resource-based view supports the development of explicit hypothesis. Different combinations of export-related resources and capabilities are identified as source of cost, product and service-type advantages and how do these advantages impact economic, strategic and relational dimensions of export performance. The findings of this study have important implications for theory, managers and policymakers. Limitations of the study are considered, and future research directions are identified.